(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
Regional ecological-economic research focuses on balancing ecological protection, economic growth, and resource utilization to achieve sustainable development. Under global climate change and environmental pressures, its significance is increasingly recognized. The System Dynamics (SD) model and the Multi-Regional Input–Output (MRIO) model serve as key quantitative tools in this research field. SD captures dynamic feedbacks and time-lag effects in complex systems, supporting long-term policy analysis. MRIO traces resource flows and environmental impacts across regions, enabling the assessment of economic–environmental linkages. Based on various scientific research projects undertaken by the research team, we have long utilized SD and MRIO models to conduct ecological-economic studies across diverse thematic areas and spatial scales. This paper systematically reviews the empirical research conducted by the authors’ team using the System Dynamics (SD) model and the Multi-Regional Input–Output (MRIO) model across various industrial sectors and spatial scales. It further explores the integration pathways of the two approaches, aiming to enrich the theoretical framework and methodological system in the field of regional ecological-economic research. Looking ahead, the research team will promote the application of SD and MRIO models in cross-border cooperation studies among China, Mongolia, and Russia, providing strong technical support for sustainable development in transboundary regions. This study holds significant theoretical importance and practical value.